The study of training needs analysis (TNA) practice in manufacturing companies in Malaysia - Abu Bakar, Khairul Asraf (2015)
Training needs analysis (TNA) has been regard as the most important steps in order to develop a successful training program as TNA can provide organizations with valuable information to help them in designing or develop strategic training programs. It has also been strongly concurred in the literature that any training intervention must begin with TNA process. Existing literature on TNA shows that most of the research and studies on organizational TNA practices were done overseas and there are limited numbers of researches from scholars that validate the effectiveness of TNA. With regard to this, this research was carried out as it is important to investigate whether Malaysian firms, in particular the manufacturing firms perform TNA before conducting any training programs for the employees. The characteristic of effectiveness of TNA practices has been researched in manufacturing companies as well. Interview with the person in charge from training department in MNC and SME company has been done to explore on TNA practices in the company. Survey questionnaire were emailed to 150 manufacturing companies listed from FMM Directory 2012 in Johor Baharu area to determine factors affecting TNA effectiveness. Data was analyzed using content and cross analysis for interview transcript and descriptive statistics for questionnaire results. The interview results shows that both MNC and SME selected company has done proper TNA process and MNC TNA is more comprehensive than SME. Questionnaire results show that involvement of employee is ranked the most important characteristic of TNA practices. Financial support characteristic to conduct TNA is least important in TNA practices